Pengaruh Independensi, Ukuran Kantor Akuntan Publik, Dan Kompetensi Terhadap Kualitas Audit - Elizabeth Bhadrika Sri Anindya (Ultima Accounting : Jurnal Ilmu Akuntansi, 2012)
The financial statement was used to show performance of the companies. The information in the financial statements should be relevant and reliable. But there are some cases of fraud in reporting the financial statements. Fraud that can not be detected by the auditor or detected but not reported by the auditor, may indicate that audit quality decreases. This research examined the effect of independence, the size of the audit firm, and competence towards audit quality. This research was conducted by using survey method, distributing the questionnaires to the auditor in big four and non big four audit firm. The method in this research study is causal study. Data analysis techniques using multiple linear regression. These results indicate that the independence and competence significantly influence the audit quality, but the size of the audit firm has no significant effect on audit quality. Also, the results of this research indicate that the independence, size of the audit firm, and competence have a significant effect simultaneously. Keyword: competence, independence, quality audit, size of the audit firm